2023
DOI: 10.1128/spectrum.04068-22
|View full text |Cite
|
Sign up to set email alerts
|

Siderophore-Based Noninvasive Differentiation of Aspergillus fumigatus Colonization and Invasion in Pulmonary Aspergillosis

Abstract: The importance of this research lies in the demonstration that siderophore analysis can distinguish between asymptomatic colonization and invasive pulmonary aspergillosis. We found clear associations between phases of fungal development, from conidial germination to the proliferative stage of invasive aspergillosis, and changes in secondary metabolite secretion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Gtx is an immunosuppressive fungal toxin that is secreted to the extracellular environment in response to fungal stress [ 40 ]. Studies have shown the utility of siderophores and/or gliotoxin in human blood and urine as useful biomarkers of Aspergillus infection, and we have detailed this recently [ 36 , 41 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gtx is an immunosuppressive fungal toxin that is secreted to the extracellular environment in response to fungal stress [ 40 ]. Studies have shown the utility of siderophores and/or gliotoxin in human blood and urine as useful biomarkers of Aspergillus infection, and we have detailed this recently [ 36 , 41 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…This method exhibited a significantly better sensitivity performance than serum sampling. It surpassed the detection accuracy of GM and BDG serology, thus providing a more effective diagnostic tool for invasive pulmonary aspergillosis [29] .…”
Section: Discussionmentioning
confidence: 99%
“…P. aeruginosa PAO1 (ATTC 15692) was purchased from the ATTC collection (Manasses, VA, USA). A. fumigatus strain EI278 was isolated from a clinical sample [ 40 ]. The media used for the growth of monocultures were Luria–Bertani broth (LB, g/L: 10 tryptone, 5 yeast extract, 10 NaCl, pH 7.0) and a minimal iron-limited medium (M9, g/L: 0.5 NaCl, 3.0 KH 2 PO 4 , 14.62 Na 2 HPO 4 × 12 H 2 O, and 1.0 NH 4 Cl, pH 7.0) supplemented with trace elements (M9TE, mg/L: 200 MgSO 4 × 7 H 2 O, 50 CaCl 2 × 2 H 2 O, 10 ZnSO 4 × 7 H 2 O, 17 MnSO 4 × H 2 O, 4.8 CoCl 2 × 6 H 2 O, 3 CuSO 4 × 5 H 2 O, 4.5 Na 2 MoO 4 ) and with glucose as a source of carbon and energy (M9TEGlu, 10 g/L).…”
Section: Methodsmentioning
confidence: 99%
“…aeruginosa PAO1 (ATTC 15692) was purchased from the ATTC collection (Manasses, VA, USA). A. fumigatus strain EI278 was isolated from a clinical sample [40]. The media used for the growth of monocultures were Luria-Bertani broth (LB, g/L: 10 tryptone, 5 yeast extract, 10 NaCl, pH 7.0) and a minimal iron-limited medium (M9, g/L: 0. )…”
Section: Microorganisms and Growth Mediamentioning
confidence: 99%